The Role of 3D Geological Modeling in Advanced Ore Body Optimization - Gupta, Ria Chopra (Journal of Progress in Civil Engineering, 2025)
The importance of three-dimensional (3D) geological modeling for understanding ore deposits is very high, especially in today's complicated mine planning environment. As mineral resources are getting scarcer and mining operations face more environmental scrutiny, the accuracy provided by 3D modeling becomes not just useful, but an essential requirement for effective and responsible resource extraction. This method improves our ability to see complex geological formations and gives a better understanding of how mineral deposits are spatially related. Such accuracy is vital for making informed decisions, as it encourages stakeholders to reconsider assumptions about ore availability and geological conditions. By bringing together various data sources - such as geological surveys, drilling information, and geophysical studies - 3D models enable a careful examination of ore distribution and quality, leading to a critical assessment of resource feasibility. Additionally, these models help evaluate risks related to geotechnical stability and environmental impact, promoting more sustainable mining practices through careful consideration of potential outcomes. This essay will outline the methods used in 3D geological modeling, spotlighting their effects on ore deposit understanding and the strategic planning needed for future mining projects.